Peculiarities of Coping and Mechanisms of Psychological Defense in Persons with Alcohol Dependence - Chkhikvadze, T.V.; Beliaeva, E.N. (Vestnik Rossiĭskogo universiteta druzhby narodov. Serii͡a︡ psikhologii͡a︡ i pedagogika, 2018)
The article is devoted to the study of the features of the defensive-coping behavior of alcohol dependent personality in the context of the necessity to optimize addiction therapy methods. An analysis of the range of coping strategies and mechanisms of psychological defense in alcoholism was conducted. The study involved 120 men and women between the ages of 30 and 60; 62 of them are patients with alcohol dependence, registered with the narcological clinic, and 58 people who do not have alcohol dependence. The following psychodiagnostic methods were used: “Strategic Approach to Coping Scale - SACS” (S. Hofball), “Life Style Index - LSI” (R. Plutchik, H. Kellerman & H.R. Conte). In the course of the analysis, it was found that behavioral pattern “aggressive actions” is expressed at a higher level in individuals with alcohol dependence. The leading coping strategies for both dependent respondents and the control sample are “seeking social support”, “cautious actions”, “coming into contact”. When assessing the gender characteristics of coping behavior, it was revealed that alcohol-dependent women use coping “avoidance” and “impulsive actions” more often than alcohol-dependent men. The dominant mechanisms of psychological defense for both dependent respondents and the control sample are “projection”, “intellectualization” and “negation”. There are differences between the group of respondents with alcohol dependence and the control group in the degree of tension of the defense mechanisms “substitution” and “compensation”: higher rates are observed in patients with alcoholism. The mechanism of defense “intellectualization” is more often and more intensively manifested in alcohol-dependent men, “reactive formations” - in alcoholdependent women. Identified in the course of the empirical study, the features are considered as possible “targets” for the psychological correction of an alcohol-dependent personality, its way of responding and behavioral stereotypes under stress.